Penelitian Atas Penyalahgunaan Dana Desa Oleh Kepala Desa di Kabupaten Bangkalan Tahun 2018 - 2023 - Mohammad Zaki (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2023)
A village is a legal community unit with household management based on rights of origin and customs recognized by the central government and domiciled in a regional district, a village is led by a village head who is elected through elections, each elected village head is responsible for the next 6 years and can re-nominate for 3 consecutive times, the village head has the duty to organize village administration, carry out development and empower the community and umkm in the village, during his tenure, a village head gets an allocation of village funds and village funds to exercise his authority over the community village.